SIMULASI MODEL TRANSPOR SEDIMEN TERSUSPENSI UNTUK MENDUKUNG PERENCANAAN PELABUHAN TELUK BAYUR, SUMATERA BARAT - Sugianto, Denny Nugroho (Jurnal Teknologi Lingkungan Universitas Trisakti, 2009)
Simulation model of suspended sediment to support development planning for Teluk Bayur port. The survey was conducted at Teluk Bayur sea waters during September 2008, where this area is development planning for Teluk bayur port. Objective of research is known suspension sediment transport at dredging area and dumping site for development planning of Teluk Bayur port at Teluk Bayur, Province of West Sumetera. Grab sampler was used to carry sediment bottom and Nansen bottle was used collect water sample for total suspended sediment (TSS). Analysis of hydrodynamic pattern used modeling system by software SMS 8.1 (Surface Water Modeling System) with SED2D module. The result had shown that TSS is above sea water standard for marine organism, between 6,0 – 10,0 mg/L. Therefore bottom sediment was dominated by sand, and then silt and gravel. The result of modeling shown that sediment transport depends of monsoon current pattern, where sediment transport to east-northeast on west monsoon and to northwest-north on east monsoon. Dredging and dumping site activity due to decreasing water quality at construction time.